PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR SISWA SUBTEMA MANUSIA DAN BENDA DI LINGKUNGANNYA - Permatasari, Shalsa Dwi; Tustiyana Windiyani; Dendy Saeful Zen (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Shalsa Dwi Permatasari, 037118075. The Effect of the Problem Based Learning Model on Student Learning Outcomes in the Sub-theme of Humans and Things in Their Environment. Thesis for Elementary School Teacher Education Study Program, Faculty of Teacher Training and Education, Pakuan University, 2023. This study used a quasi-experimental research type with a two-class design. The purpose of this study was to determine the effect of the Problem Based Learning model on learning outcomes for the Sub-theme of Humans and Objects in their Environment. The subjects of this study were students in grades V-A and V-B of Benda State Elementary School, Sukabumi Regency, even semester of the 2022/2023 academic year, with a total of 66 students. The results showed that there was a significant difference in the average value of N-Gain and completeness in the learning outcomes of the experimental class (Problem Based Learning) and the control/conventional class (Discovery Learning). The average N-Gain score in the experimental group was 61.24 with 94% completeness, while the average N-Gain in the control class was 43.00 with 69% completeness. The results of the hypothesis test stated that Ho was rejected and Ha was accepted, because tcount (2.1038) > ttable (1.81072) with dk 64 and a significance level of 0.05 (5%). Based on the results of this study, it can be concluded that there is an effect of applying the Problem Based Learning model to learning outcomes for the Sub-theme of Humans and Things in Their Environment in class V Benda State Elementary School, Sukabumi Regency, Even Semester for the 2022/2023 school year.